Development of business skills at SMK ICB Cinta Niaga using project-based learning methods - Anggia Rachman Fauzan; Muhamad Fajrul Falah Khoiri; Nasywa Devinta Arifian (Universitas Pendidikan Indonesia, 2024)
This study investigates the utilization of Project-Based Learning (PBL) in SMA ICB Cinta Niaga to enhance students' business skills. PBL emphasizes applying knowledge in real-life situations, starting from concrete problems or projects. The method effectively boosts students' motivation by actively engaging them in learning. The research employs a qualitative descriptive approach with interviews as the primary data collection method. The study aims to evaluate the effectiveness of PBL in improving students' skills. Interviews with teachers and students at SMK ICB Cinta Niaga reveal the positive impact of PBL. Teachers acknowledge its role in developing business skills, while students experience significant benefits in honing their abilities. PBL creates a collaborative learning environment with challenges that encourage students to be active and responsive to problems. The study concludes that PBL at SMK ICB Cinta Niaga positively contributes to developing students' business skills. The method not only enhances learning motivation but also sharpens students' social skills in problem-solving. These conclusions are drawn from teacher experiences and student perceptions, portraying PBL as an effective and beneficial learning method for developing business skills in this educational context.